THE INFLUENCE OF STRATEGY IMPLEMENTATION ON COMPETITIVE ADVANTAGE - Ka Utama, Hendri; Sari, Rela (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study analyzes the influence of strategy implementation on competitive advantage through a Systematic Literature Review (SLR) using the PRISMA approach (methodological keyword). Based on an analysis of 30 articles indexed in Scopus and Emerald (2018–2025), findings show that 96.7% of studies support the positive impact of strategy implementation when it meets the VRIO criteria (valuable, rare, inimitable, organized) from the Resource-Based View (RBV) theory (theoretical keyword). The dominance of RBV (8 out of 30 articles) confirms that unique internal resources such as digital capabilities and service innovation are key drivers of competitive advantage in the manufacturing and digital economy sectors (contextual keyword). Major challenges include the strategy implementation gap (planning-execution discrepancy) and organizational resistance, particularly among SMEs. This study also integrates the perspective of dynamic capabilities (sensing, seizing, reconfiguring) to address the dynamics of disruptive markets. Practical implications include recommendations for companies to adopt data-driven strategic management systems and ecosystem-based collaboration (ecosystem strategy). Academically, this research enriches the literature with a multidisciplinary synthesis and a future research agenda on strategic adaptation in emerging economies.